Merjenje spletnega oglaševanja in aktivnosti uporabnikov Interneta - Kogovšek, Luka (Teorija in praksa, 2000)
The paper deals with the most frequently used methods for measuring Web users'activities, with a special focus on Internet advertising related topics.Further, three methods for measuring Web site visits and counting number of interactions with advertising items (web-server centric, ad-server centric, user centric method), commonly used to provide information, are discussed and compared.
Keywords: Measurement; Merjenje; Advertising; Internet; Oglaševanje; informacijska tehnologija; information technology; spletne strani; tržno komuniciranje; raziskave